Global Health and Human Rights : Principles and Practices - Hamelink, Cees J., 1940-; Essink, Dirk R.; Visser, Marlies J. (London : Routledge, 2025)
This textbook explores public health and individual health care through the prism of global human rights and ethical decision-making. Written by leading experts in this field, the book is divided into three distinctive parts. Part I introduces the theoretical framework through which the core issues can be understood, contrasting a clinical approach to health care with a social determinant perspective and discussing the decolonialisation of global health. Part II discusses how a human rights rationale impacts different social groups, from children to the elderly to those with disabilities, highlighting issues such as abortion and euthanasia. Part III addresses contemporary topics such as infectious diseases, migration, mental health care, the impact of advanced medical technology and climate change. Each chapter features case studies which ask readers to assess complex ethical dilemmas, fostering decision-making based on clear moral reasoning, as well as discussion assignments and further reading. Also featuring online video lectures, this is an important textbook that will be essential reading for students across the health sciences, including medicine and all related fields.
Keywords: MEDICAL / Public Health; MEDICAL / Ethics; Right to health; Public health laws, International; World health; Human rights